ANALISIS PENGARUH KETIMPANGAN WILAYAH TERHADAP PEMBANGUNAN DI KABUPATEN PUNCAK PAPUA - Rudy Mom; Harmonis Rante; Bernathius Julison (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2023)
Inequality Interagency Development Region or area is problem development yet can abolished especially in temperate countries growing. Regency Peak Central Papua Province, has level inequality of regional development between districts up to the high villages when compared to with Other districts in Central Papua Province. Study This aim For analyze Influence level regional inequality in the district peak, prove Kuznets hypothesis, as well analyze influence variable independent of GRDP per capita, investment, agglomeration, and decentralization dummy fiscal to inequality regional development in the District Peak in period 2009 until by 2023. Study This using primary and secondary data consisting from condition data field related Development inequality between regions districts throughout the district peak, method analysis used _ For study This is analysis Qualitative and Descriptive. Research results This showing that condition inequality between regions in the district the peak is very high, so government need have a good strategy in making plans extension Long term, term short nor middle, deep handle comparison of the resulting regions No happen increasea development progress between regions in the district in general.